2018
DOI: 10.2215/cjn.03170318
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experience with Primary Care Physician and Risk for Hospitalization in Hispanics with CKD

Abstract: Background and objectivesIn the general population, the quality of the patient experience with their primary care physician may influence health outcomes but this has not been evaluated in CKD. This is relevant for the growing Hispanic CKD population, which potentially faces challenges to the quality of the patient experience related to language or cultural factors. We evaluated the association between the patient experience with their primary care physician and outcomes in Hispanics with CKD.Design, setting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…These challenges lead to later hospital presentation, low healthcare utilization, and poor outcomes. 4,11,29,42,64,65 The US healthcare system finds itself in an unfortunate cycle with some of its most socially marginalized patients. Additional research is needed; however, it may be challenging to conduct research on the Latinx community given reports of mistrust of medical researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges lead to later hospital presentation, low healthcare utilization, and poor outcomes. 4,11,29,42,64,65 The US healthcare system finds itself in an unfortunate cycle with some of its most socially marginalized patients. Additional research is needed; however, it may be challenging to conduct research on the Latinx community given reports of mistrust of medical researchers.…”
Section: Discussionmentioning
confidence: 99%
“…A survey that assessed satisfaction among Latinx patients with LEP and kidney disease reported an association between poor patient clinic satisfaction and increased risk of hospitalization which could not otherwise be explained by medication nonadherence, hemoglobin A1c, or blood pressure. 4 Poor patient satisfaction can also affect patients' access to care. Interviews with patients with LEP demonstrated that compared to patients with high satisfaction, those with low satisfaction were less likely to return to the emergency department for care.…”
Section: Introductionmentioning
confidence: 99%
“…30 Any hospitalizations falling within a "disease of the circulatory system" category was designated as cardiovascular; all others were deemed non-cardiovascular. 31 Ascertainment of ESKD was supplemented by cross-linkage with the US Renal Data System. Deaths were ascertained from reports by next of kin, death certificates, hospital records, and linkage with the Social Security Death Master File.…”
Section: Discussionmentioning
confidence: 99%
“…Even when they have insurance coverage, the majority of these patients depend on primary care providers (PCP) for kidney-related care as a result of limited access to nephrologists. Unfortunately, there is often suboptimal quality of CKD education during encounters with PCP in the localities in which marginalized populations live ( 42 44 ). It is, therefore, necessary to work with community PCP to enhance their knowledge about the nature and complications associated with kidney disease.…”
Section: Structural Barriers To Accessing Kidney Servicesmentioning
confidence: 99%